GOATFISH (MULLIDAE) RESOURCES IN VIETNAM SEA BASED ON BOTTOM TRAWL SURVEY IN THE PERIOD 2012 - 2013 - Thang, Vo Trong; Cuong, Tran Van; Nhuan, Mai Cong; Hai, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2018)
During 2012 - 2013, under the project “The current status and movements of fisheries resources in Vietnam sea” two surveys were conducted to investigate bottom fish resources with 494 hauls. Based on the research results, 16 species belonging to 3 genera of goatfishes were analyzed. The goatfish output accounted for 0.34 - 4.31% compared to the total output of bottom fish in the survey time. The species Upeneus japonicus comprised 62 - 94% of the output of the goatfishes. The average exploitation yield of goatfishes in the Northeast monsoon season was 1.035 kg/h and that in the Southwest monsoon season was 1.446 kg/h. The exploitation yield had a tendency of decrease compared with the previous studies. The distribution density was the highest in the Southwestern region areas and the lowest in the Gulf of Tonkin; Meanwhile according to spatial distribution the density of goatfishes was the highest in the depth < 20 m and the lowest in the depth from 30 - 50 m. The estimation for the total biomass of goatfishes in the Northeast monsoon season was 13,450 tons and in the Southeast monsoon season was 15,321 tons